2021
DOI: 10.1136/bmjresp-2021-000996
|View full text |Cite
|
Sign up to set email alerts
|

The physiology of singing and implications for ‘Singing for Lung Health’ as a therapy for individuals with chronic obstructive pulmonary disease

Abstract: Singing is an increasingly popular activity for people with chronic obstructive pulmonary disease (COPD). Research to date suggests that ‘Singing for Lung Health’ may improve various health measures, including health-related quality-of-life. Singing and breathing are closely linked processes affecting one another. In this narrative review, we explore the physiological rationale for ‘Singing for Lung Health’ as an intervention, focusing on the abnormalities of pulmonary mechanics seen in COPD and how these migh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
24
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 74 publications
0
24
0
1
Order By: Relevance
“… 20 36 41 44 However, specific physiological changes have not been convincingly confirmed. 2 4 20 42 In accordance with formerly posed requests, 2 the present study explored whether SLH might be associated with change in any detectable physiological parameters specifically focusing on measures reflecting lung function, inspiratory muscle strength and control, dyspnoea and breathing control, and exercise-induced changes in pulse and saturation.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“… 20 36 41 44 However, specific physiological changes have not been convincingly confirmed. 2 4 20 42 In accordance with formerly posed requests, 2 the present study explored whether SLH might be associated with change in any detectable physiological parameters specifically focusing on measures reflecting lung function, inspiratory muscle strength and control, dyspnoea and breathing control, and exercise-induced changes in pulse and saturation.…”
Section: Discussionmentioning
confidence: 85%
“…The recent narrative review 2 suggested that singing may improve aspects in breathing pattern, respiratory control, hyperinflation, dyspnoea, health-related QoL, and interoception. Improved physical capacity and activity has likewise been reported in some previous studies besides enhanced respiratory well-being.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The theoretical premise for the effect of singing on breathlessness has been explored in the context of COPD and can result in altered breathing mechanics. 8 Interestingly, in Philip and colleagues' study, breathlessness did not significantly improve between groups using the dyspnoea-12 or visual analogue scale (VAS) for rest and walking, but did demonstrate improvements in the VAS running score. It is possible that this was a result of the participants' interpretation of the question and the recall required to interpret their breathlessness experiences.…”
mentioning
confidence: 91%